Information science and the new information technologies : a bibliography (Caribbean Documentation Centre Port of SpainTT, 1987)
Bibliography focusing on recent developments in the information field with implications for the Caribbean. Covers areas including the economics of information, information systems/networks, information policy, informatics, telematics and transborder data flows. Includes author and title indices.
IDS